Rural funerals – yesterday and nowodays (basing on the example of the village of Smardzów) - Szczepańska, Beata (Wiejskie pogrzeby wczoraj i dziś (studium przypadku wsi Smardzów), 2018)
The aim of the study was to try to obtain answers to the following questions: What changes have appeared in the funeral ritual in Polish countryside in the last 60 years and: Can these processes be included in the crisis of death? The research was carried out among women residents of Smardzów, situated 24 kilometres north-east of Wrocław. There were 12 interviews carried out. A research technique used in order to obtain interesting data, constituted an interview with a standardised number of questions. According to the answers of many responders, it is possible to find a lot of changes in funeral rite. Those answers indicate the crisis of death. We no longer deal with death as a public event, people rather die alone in hospitals, not surrounded with their family at home. The funeral celebration has been limited dramatically. The most attention is given to the organization of a funeral feast. All these phenomena are part of the concept of the crisis of death.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2018; Nr 534, s. 116-126
Keywords: funeral ritual; rural communities; rural areas; rytuały pogrzebu; społeczności wiejskie; obszary wiejskie